Faktor-faktor yang Berhubungan dengan Learning Agility: A Systematic Literature Review - Gresika Tabitha Vinesian; Suryanto Suryanto; Reza Lidia Sari (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
The current situation in the world is experiencing VUCA, where there are rapid and drastic changes in technology, economics, the environment, and other aspects. Every adult, especially employees and job seekers, needs to develop learning agility so that they can adapt and compete in today's era. This systematic literature review aims to identify the factors related to learning agility. Article searches were conducted from March to June 2022 using six databases, namely SpringerLink, Emerald Insight, ScienceDirect, SAGE, Scopus, and ProQuest, with keywords "Learning Agility" AND "Employee*" OR "Jobseeker*" OR "Student*". After the article screening process, a total of 10 studies were obtained and analyzed in this literature review. The results show that there are 11 factors related to learning agility, namely compensation, salary, internal marketability, digital competence, digital technologies, e-learning, career variety, work experience, outcome, learning engagement, dan turnover intention. The results of this study can be useful as a reference for future research to further examine the relationship of the above factors. The results of the study can also be practically useful for developing individual learning agility so that they have optimal potential to adapt agilely in the VUCA era.